CONTROL AND GRID SYNCHRONIZATION OF TWO LEVEL VOLTAGE SOURCE INVERTER UNDER TEMPORARY VOLTAGE UNBALANCE - Chmielewski, Tomasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
This paper presents the operation of grid tied, two level voltage source inverter (VSI) during network voltage unbalance. The control system was implemented in synchronous rotating reference frame dq0 (SRF). Two types of control structures were investigated herein. First utilizes the Double Decoupled SRF Phase-locked loop (DDSRF-PLL) synchronisation with positive and negative sequence currents control. Second one is simplified system that does not provide symmetrical components decomposition and decoupling for synchronisation. Simulation results exhibited a superior performance of the DDSRF-PLL control system under grid voltage unbalance.